Longitudinal Assessment of Immune Responses to Repeated Annual Influenza Vaccination in a Human Cohort of Adults and Teenagers - Sung, Meng-Hsuan; Shen, Ye; Handel, Andreas; Bahl, Justin; Ross, Ted M. (Frontiers in Immunology, 2021)
Background. The overall performance of a multiple component vaccine assessed by the vaccine-elicited immune responses across various strains in a repeated vaccination setting has not been well studied, and the comparison between adults and teenagers is yet to be made. Methods. A human cohort study was conducted at the University of Georgia, with 140 subjects (86 adults and 54 teenagers) repeatedly vaccinated in the 2017/2018 and 2018/2019 influenza seasons. Host information was prospectively collected, and serum samples were collected before and after vaccination in each season. The association between host factors and repeated measures of hemagglutination inhibition (HAI) composite scores was assessed by generalized linear models with generalized estimating equations. Results. The mean HAI composite scores for the entire sample (t=4.26, df=139, p-value<0.001) and the teenager group (t=6.44, df=53, p-value<0.001) declined in the second season, while the changes in the adults were not statistically significant (t=-1.14, df=85, p-value=0.26). A mixture pattern of changes in both directions was observed in the adults when stratified by prior vaccination. In addition, the regression analysis suggested an interactive effect of age and BMI on the HAI composite scores in the overall population (beta=0.005; 95% CI, 0.0008 to 0.01) and the adults (beta=0.005; 95% CI, 0.0005 to 0.01). Conclusions. Our study found distinct vaccine-elicited immune responses between adults and teenagers when both were repeatedly vaccinated in consecutive years. An interactive effect of age and BMI on the HAI composite scores were identified in the overall population and the adults.